Formulation of Nanoemulsion Gel Cayenne Pepper (Capsicum frutescens) Extract as an Anti-inflammatory in Gout Arthritis Pain - Amilia Salsabila; Rahma Aprilya Jonisa; Yasmin Raudhatul Jannah; Vannesha Yuningzia; Aulia Desvita Sari; Henny Lucida (Fakultas Farmasi Universitas Andalas, 2025)
Cayenne pepper fruit extract has anti-inflammatory effects and could be a natural remedy of arthritis gout pain. The research aims to find the optimal formula for cayenne pepper extract nanoemulsion gel to improve its permeation capability and assess its effect on inflammation in mice induced by 1.5% carrageenan. Extraction using the maceration method followed by standardizing the extract. The optimal nanoemulsion formula is determined by constructing a pseudo-ternary diagram of the nanoemulsion base. The optimal formula obtained was 80% aquadest, 2% VCO, 18% SMIX (surfactant and cosurfactant). The cayenne pepper extract nanoemulsion is integrated with a gel base followed by evaluation. The extract nanoemulsion has been proven to form globules with a size of 54.4 nm, zeta potential of -23.6 mV, and polydispersity index of 0.403. Exudate volume and TNF-α levels were measured using the air pouch method to assess for anti-inflammatory activity. In comparison to other treatment groups, rats treated with chili pepper extract nanoemulsion gel had the lowest average exudate volume, with a statistically significant difference (DNMRT; P <0.05), according to the results of an ANOVA test combined with Duncan's post-hoc test. Meanwhile, the test for TNF-α levels did not show any significant differences